2004
DOI: 10.1017/s0147547904000171
|View full text |Cite
|
Sign up to set email alerts
|

Laboring Across National Borders: Class, Gender, and Militancy in the Proletarian Mass Migrations

Abstract: A decade-long project on the migration of Italian laborers around the world during the nineteenth and twentieth centuries points to the methodological challenges, theoretical debates, and some of the rewards of transnational analysis of class, ethnicity, and gender in the making of modern national states. Analyses of internationally mobile laborers historicize current transnational studies, problematize the historiography of national groups, and reveal how profoundly—and usually also how “nationally”—every mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Scholars including Franca Iacovetta, Donna Gabaccia, and Fraser Ottanelli, for example, have pointed out that labour historians' preoccupation with notions of respectable womanhood have been framed in reference to Anglo-Canadian and Anglo-American notions of femininity and may not necessarily be applicable to immigrant women. 22 Similarly, Ruth Frager and Roz Usiskin have suggested that Jewish-Canadian immigrant garment workers approached labour activism in ways inspired by traditions of leftist radicalism deeply entrenched in Jewish culture. 23 Frager argues that Jewish homeland culture, though changed in North American environments, often contained ideals of female respectability that did not necessarily preclude acts of public protest or labour activism.…”
mentioning
confidence: 99%
“…Scholars including Franca Iacovetta, Donna Gabaccia, and Fraser Ottanelli, for example, have pointed out that labour historians' preoccupation with notions of respectable womanhood have been framed in reference to Anglo-Canadian and Anglo-American notions of femininity and may not necessarily be applicable to immigrant women. 22 Similarly, Ruth Frager and Roz Usiskin have suggested that Jewish-Canadian immigrant garment workers approached labour activism in ways inspired by traditions of leftist radicalism deeply entrenched in Jewish culture. 23 Frager argues that Jewish homeland culture, though changed in North American environments, often contained ideals of female respectability that did not necessarily preclude acts of public protest or labour activism.…”
mentioning
confidence: 99%